Uncommon cervical pain due by Bacillus pumilus spondylodiscitis in an immunocompetent patient: a case report.: Bacillus pumilus spondylodiscitis - Fusini, Federico; Colò, Gabriele; Massè, Alessandro; Girardo, Massimo (Acta Biomedica Atenei Parmensis, 2021)
A fifty-three year-old military patient, presented with a 3 months neck pain and paraesthesia of upper right extremity after gastroscopy. Radiological examination demonstrated anuncertain degenerative/infective involvement of C6-C7 intervertebral disc. The patient underwent anterior debridement with C5-C6 disc excisional biopsy, with microbiological findings of Bacillus pumilus with high bacterial concentration. After biopsy, segment arthrodesis was achieved only with vertebral plate cruentation and 3 months of cervical collar. He completed a six-weeks course of intravenous antibiotics for the treatment of atypical spondylodiscitis. At one year of follow-up, he had no residual neck pain or neurological signs or symptoms.